AUTENTISITAS SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN (SKMHT) FORMAT PERATURAN KEPALA BADAN PERTANAHAN NASIONAL NOMOR 8 TAHUN 2012 YANG DIBUAT OLEH NOTARIS DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 30 T - PERIS MAHA (PREMISE LAW JURNAL, 2018)
Government Regulation No. 24/1997 on Land Registration (henceforth, PP on Land Registration) regulate the implementation of land registration stipulated in Article 19 of UUPA. Legal provision found in Perkaban No 8/2012 which is the administrative regulation of PP No 24/1997 as the administrative regulation of UUHT. The imposition of Perkaban No 8/2012 which determines SKMHT has to be made in the form of Notarial or PPAT deed. Based on the provision in Article 1868 of the Civil Code, a notarial deed can be considered authentic provided that it meets the requirements as follows: 1) the Deed has to be made “by” (door) or before (ten overstan) a public official, 2) the Deed has to be made in the form determined by law, 3) the public official has to have the authority to draw up that Deed.Keywords: Authenticity, Power of Attorney on Burdening Hypothecation, Directive of the Head of the National Land Agency, Notary, Law No. 2/2014 on Amendment of Law No. 30/2004 on Notarial Position